1977
DOI: 10.1128/jvi.22.2.553-560.1977
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Escherichia coli membrane by addition of bacteriophage T4 protein synthesized after infection

Abstract: Many T4-induced proteins were found associated with the Escherichia coli membrane during infection. Some of these were apparently sonically bound, but many could be identified as integral parts of the inner and outer bacterial membranes by their selective solubilities in guanidine or Sarkosyl. The synthesis and insertion of these proteins into the bacterial membrane were temporally controlled and, once in the membrane, these proteins were stably integrated. Host membrane protein synthesis continued after infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Group 3 resembles the smaller T-phages of Escherichia coli (25). It is known that certain phages of E. coli cause the insertion of new proteins into the plasma t Present address: Laboratory of Microbial Structure and Function, National Institute of Allergy and Infectious Disease, Rocky Mountain Laboratory, Hamilton, MT 59840. membrane (8,39) and also affect membrane lipid synthesis (28). The latter phenomenon is particularly significant for amber mutants of the filamentous coliphage fl(M13) (28).…”
mentioning
confidence: 99%
“…Group 3 resembles the smaller T-phages of Escherichia coli (25). It is known that certain phages of E. coli cause the insertion of new proteins into the plasma t Present address: Laboratory of Microbial Structure and Function, National Institute of Allergy and Infectious Disease, Rocky Mountain Laboratory, Hamilton, MT 59840. membrane (8,39) and also affect membrane lipid synthesis (28). The latter phenomenon is particularly significant for amber mutants of the filamentous coliphage fl(M13) (28).…”
mentioning
confidence: 99%
“…Two studies on the modification of host cell membranes by phage-induced proteins published since our work was done also described a quantitative association of gp46 with the host cell membranes and spheroplast envelopes (16,55). gp47 was not identified in either of these studies.…”
Section: Downloaded Frommentioning
confidence: 84%
“…By this criterion, although we found that gp47 was membrane associated, it also is not an integral membrane protein since incubation with NaClO4 released it from membranes. However, solubilization of a protein by chaotropic agents does not rule out the possibility that the protein has a functional interaction with the membrane (10,16,34,45), but it does show that the binding interaction is probably ionic.…”
Section: Downloaded Frommentioning
confidence: 99%
“…infection. Altematively, the late function may increase membrane fragility directly by modifying the membrane; changes in membrane composition after infection have been reported (11,12,15,21,34,46,51). Furrow and Pizer (15) have found that after T4 infection the relative rates of 32p; incorporation into phosphatidylglycerol and phosphatidylethanolamine were altered.…”
Section: -mentioning
confidence: 99%